Oxycodone Self-Administration Induces Alterations in Expression of Integrin, Semaphorin and Ephrin Genes in the Mouse Striatum - Yuferov, Vadim; Zhang, Yong; Liang, Yupu; Zhao, Connie; Randesi, Matthew; Kreek, Mary J. (Frontiers in Psychiatry, 2018)
Introduction. Oxycodone is a commonly used medication for pain, and is also a widely abused prescription opioid. Neurochemical and structural adaptations in brain following chronic MOPr-agonist administration are thought to underlie pathogenesis and persistence of opiate addiction. Many axon guidance molecules may contribute to oxycodone-induced neuroadaptations through alterations in axon-target connections and synaptogenesis, and these may be implicated in the behaviors associated with opiate addiction. However, little is known about this important area. The aim of this study is to investigate alterations in expression of selected integrin, semaphoring, ephrin, netrin, and slit genes in the nucleus accumbens and caudate putamen of mice, following extended 14-day oxycodone self-administration (SA), using RNAseq. Methods. Total RNA from the NAc and CPu were isolated from adult male C57BL/6J mice within 1 h after the last session of oxycodone in a 14-day self-administration paradigm (4h/day, 0.25 mg/kg/infusion, FR1) or from yoked saline controls. Gene expressions were examined using RNA sequencing (RNA-Seq) technology. RNA-Seq libraries were prepared using the Illumina TruSeq® Stranded Total RNA LT kit. DESeq2 was applied to estimate the fold change between the treatment groups. False Discovery Rate (FDR) q< 0.1 was used to select genes that had a significant change in expression. Results. After oxycodone self-administration, among known genes of the integrin, semaphorin, and ephrin gene families, RNA-seq data revealed up-regulation of six genes in the NAc: integrins Itgal, Itgb2 and Itgam, and semaphorin Sema7a, two semaphorin receptors, plexins Plxnd1 and Plxdc1. There was down-regulation of eight genes in this region: integrin genes Itga3 and Itgb8, semaphorins Sema3c, Sema4g, Sema6a, Sema6d, semaphorin receptor neuropilin Nrp2, and ephrin receptor Epha3. In the CPu, there were five differentially expressed axon guidance genes: up-regulation of three integrin genes, Itgal, Itgb2, Itga1, and down-regulation of Itga9 and ephrin Efna3 were thus observed. Conclusion. We provide evidence for alterations in the expression of selective axon guidance genes in adult mouse brain, following chronic self-administration of oxycodone. Further examination of oxycodone-induced changes in the expression of these specific axon guidance molecules genes in relation to behavior may provide new insights into development of addiction to oxycodone